2018
DOI: 10.3390/nu10060778
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Influence on Body Fluid Acid-Base and Volume Balance: The Deleterious “Norm” Furthers and Cloaks Subclinical Pathophysiology

Abstract: The popular modern diet, characterized by an excess of animal protein and salt but insufficient in fruits, vegetables and water, is a poor fit for human physiological and homeostatic regulatory systems. Sustained net acid and sodium retention, coupled with an insufficient intake of cardiovascular protective potassium-rich foods and hydration in the modern diet can give rise to debilitating chronic organ dysfunction and ultimately, mortality. This holds true, especially in our aging population who are already f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 109 publications
1
4
0
3
Order By: Relevance
“…Although wastes and the products of metabolism contribute to extracellular osmolality (P OSM and S OSM ), dietary energy content (Kcal) accounts for 85% of the variance in ROE. Thus, Panel A supports the concept that renal osmolar load each day is largely influenced by diet [93,101,[126][127][128] and agrees with the dietary modification plan advanced by Amro and colleagues in 2016 (i.e., which led to reduced plasma AVP and a reduced TWI requirement for AVP reduction in kidney disease patients) [128]. In contrast, the correlation between TWI and ROE ( Figure 7, Panel B) is weaker (R 2 = 0.29).…”
Section: Reduce 24-h Osmolar Loadsupporting
confidence: 83%
See 3 more Smart Citations
“…Although wastes and the products of metabolism contribute to extracellular osmolality (P OSM and S OSM ), dietary energy content (Kcal) accounts for 85% of the variance in ROE. Thus, Panel A supports the concept that renal osmolar load each day is largely influenced by diet [93,101,[126][127][128] and agrees with the dietary modification plan advanced by Amro and colleagues in 2016 (i.e., which led to reduced plasma AVP and a reduced TWI requirement for AVP reduction in kidney disease patients) [128]. In contrast, the correlation between TWI and ROE ( Figure 7, Panel B) is weaker (R 2 = 0.29).…”
Section: Reduce 24-h Osmolar Loadsupporting
confidence: 83%
“…To the contrary, Allen and colleagues [42] concluded that S Na+ levels in the upper half of the "normal range" should be treated as a clinical risk factor that prompts recommendation for modification of water and salt intake. Their conclusion suggests that not all "normal" laboratory blood values represent a similar risk of chronic disease [93]. Further, if this paradigm of disease risk ( Figure 5) is verified, educational campaigns that are designed to increase water intake in healthy individuals, especially low volume consumers, will become important for modifying drinking habits and lower the risk of chronic diseases in LOW.…”
Section: A Theoretical Paradigm Of Disease Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary and nutritional optimization, for example, regarding the achievement of a better dietary potassium/sodium ratio, is still not a highly emphasized area of health care. However, it has a great potential to attenuate the impact of prevalent chronic diseases in modern society (including BC) and improve population health [56]. In light of the implications of dietary acid load, although further studies are needed to confirm the present study's findings, we are convinced that from a medical and ethical viewpoint, it is justified to recommend -as we did one decade ago [57]-certain nutritional changes to women, because in the meantime no adverse side effects are expected to occur.…”
Section: Resultsmentioning
confidence: 99%